HR Analytics in the IT Sector: Linking Performance Appraisal Practices with Employee Engagement - Muskan Saxena, Vibhor Jain (European Economic Letters (EEL), 2025)
In an increasingly data-driven corporate landscape, Human Resource (HR) analytics has emerged as a pivotal tool in shaping strategic HR decisions. Within the IT sector—an industry marked by high competition, dynamic work environments, and a skilled workforce—leveraging HR analytics for effective performance appraisal has gained significant attention. This study investigates the extent to which HR analytics tools and techniques are integrated into performance appraisal processes and examines their influence on employee engagement levels. The research adopts a mixed-method approach, combining quantitative data gathered through structured surveys with qualitative insights from interviews conducted with HR professionals and employees in leading IT firms. The study aims to identify prevalent HR analytics practices, assess their effectiveness in appraising performance, and explore the correlation between data-driven performance evaluation and employee engagement metrics such as motivation, satisfaction, and retention. Findings from the research are expected to reveal that the strategic use of HR analytics not only enhances objectivity and transparency in performance appraisal but also fosters a more engaged and motivated workforce. Moreover, the study seeks to highlight best practices and challenges associated with HR analytics adoption in the IT sector. This research contributes to both academic understanding and practical implementation by bridging the gap between analytical performance management and human-centered employee engagement strategies. It underscores the growing need for IT organizations to align technological tools with human resource development, ensuring that data-driven decisions do not merely quantify employee output but also enhance their overall experience and involvement in the organization.